An SMS fiber structure for seismocardiography (SCG) monitoring - F.R. Agustiyanto; A.M. Hatta; D. Arifianto; M. Radityo; P.S. Maulana; B.S. Pikir (Results in Optics)
A singlemode-multimode-singlemode (SMS) fiber structure for seismocardiography (SCG) monitoring that utilizes a simple intensity-based interrogation system is proposed in this letter. The vibration response of the SMS fiber structure utilized as a sensor is investigated experimentally. It is found that a linear vibration response of the SMS fiber structure within a frequency range of 0–180 Hz can be utilized for SCG monitoring that requires a low-frequency range of 0–25 Hz. The measured optical power of the SMS fiber structure was processed using filtering leads to SCG signal. It is also found that the placement of the sensor in the chest can vary the SCG signal. The proposed SCG sensor offers a simple configuration and low cost compared to other fiber optic SCG sensors.